Managerial Reputation and the Informativeness of Accounting and Market Measures of Performance* - JOHNSON, W. BRUCE; YOUNG, S. MARK; WELKER, MICHAEL (Contemporary Accounting Research, 1993)
Abstract. This study examines the influence of accounting and capital market measures of firm performance on the reputations of corporate chief executives (CEOs). The empirical tests rely on pooled time‐series cross‐sectional data for approximately 900 top executives in about 500 firms drawn from 36 industries over the 1975–1987 period. CEO reputation measures are derived from securities analysts' annual evaluations of executive performance as reported by Financial World magazine. The study's results document a positive incremental association between profit performance and reputation, a finding consistent with the notion that accounting earnings convey information about CEO productivity beyond that present in stock returns. However, the sensitivity of CEO reputation to stock returns and earnings performance is modest, and the earnings‐reputation relation varies considerably across industry groups. Résumé. Les auteurs s'intéressent ici à l'influence qu'exercent sur la réputation des directeurs généraux de sociétés les mesures de la performance de l'entreprise relevant de la comptabilité et du marché des capitaux. Leurs tests empiriques s'appuient sur les données transversales de séries chronologiques groupées relatives à environ 900 cadres supérieurs de quelque 500 entreprises provenant de 36 secteurs d'activité, relevées entre 1975 et 1987. Les « mesures » de la réputation des directeurs généraux de sociétés sont dérivées de l'évaluation annuelle de la performance des cadres, produite par les analystes en valeurs mobilières, dont fait état le magazine Financial World. Les résultats obtenus révèlent une association prenant la forme d'un écart marginal positif entre la performance, en termes de profits, et la réputation, constatation qui corrobore la notion selon laquelle les bénéfices comptables livrent, au sujet de la productivité des directeurs généraux de sociétés, de l'information que ne livre pas le rendement des actions. La sensibilité de la réputation des directeurs généraux de sociétés au rendement de l'action et aux bénéfices est cependant modérée, et la relation bénéfices‐réputation varie largement selon les groupes sectoriels.